Anemia and Contributing Factors in Severely Malnourished Infants and Children Aged between 0 and 59 Months Admitted to the Treatment Centers of the Amhara Region, Ethiopia: A Multicenter Chart Review Study - Wubet Worku Takele; Adhanom Gebreegziabher Baraki; Haileab Fekadu Wolde; Hanna Demelash Desyibelew; Behailu Tariku Derseh; Abel Fekadu Dadi; Eskedar Getie Mekonnen; Temesgen Yihunie Akalu (Anemia)
Background. Anemia among severely malnourished children is a double burden that could make the treatment outcome of severe acute malnutrition (SAM) more unfavorable. The burden and the factors are, however, uncovered among children in the Amhara region. Therefore, the study was aimed at determining the prevalence of anemia and identifying contributing factors in severely malnourished children aged between 0 and 59 months admitted to the treatment centers of the Amhara region referral hospitals. Methods. A facility-based cross-sectional study was conducted that included 1,301 infants and children, who developed SAM and were admitted to the three referral hospitals of the Amhara region. Data were extracted using a data extraction checklist. The binary logistic regression analysis was employed to show an association between the dependent and independent variables. Multicollinearity was assessed using the variance inflation factor (VIF) and no problem was detected (overall VIF = 1.67). The presence of association was declared based on the p-value (≤0.05), and the adjusted odds ratio with its respective 95% confidence interval was used to report the direction, as well as the strength of association. Results. About 41.43% (95% CI: 38.78%–44.13%) of severely malnourished infants and children have developed anemia, of which around half (47%) of them were under six months old. Rural residence (AOR = 1.56; 95% CI: 1.14–2.12) and HIV infection (AOR = 2.00; 95% CI: 1.04–3.86) were significantly associated with higher odds of anemia. Furthermore, being exclusively breastfed (AOR = 0.57; 95% CI 0.39–0.83) remarkably reduced the likelihood of anemia. Conclusions. This data confirms that anemia among severely malnourished infants and children is a public health problem in the Amhara region. Infants younger than six months were at a higher risk of anemia. Being a rural resident and contracting HIV infection have elevated the occurrence of anemia, whereas being exclusively breastfed decreased the risk. Therefore, the study gives an insight to policymakers and planners to strengthen the existing exclusive breastfeeding practice. Strategies being practiced to prevent HIV transmission and early detection, as well as treatment, should also be strengthened. Furthermore, mothers/caretakers of infants and children residing in the rural areas deserve special attention through delivering nutrition education.